PENGARUH PENGGUNAAN MEDIA GRAFIS TERHADAP HASIL BELAJAR SISWA KELAS VIII MATA PELAJARAN IPS TERPADU SMP NEGERI 2 KALIREJO - Munfahiroh Nafisah; Maryatun Maryatun (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to investigate the influence of graphic media on student learning outcomes. The type and design of the study were in the form of research Quas Experiment design. The population of the study was 132 students. Determination of control groups and experiments was carried out through certain considerations. Data was collected through test trials and data were analyzed by inferential statistics (t-test). The results showed that there were significant differences in the learning outcomes of students learning with mediagraphics and students who studied with conventional learning methods. This was evidenced by the tcount of 2.593 and ttab = 1.71, the tcount was greater than ttab. Based on the results of this study it can be said that students who study with graphic media show higher results than students who learn with conventional learning methods. Keywords: Graphic Media, Learning Outcomes